The National and International Studio Artists Program 1993-94. - Avgikos, Jan; PS1 Contemporary Art Center, New York (New York : Institute for Contemporary Art, 1994)
Beattie, Drew ; Davidson, Daniel ; Bevan, Tom ; Büsch, Thomas ; Dahl, Cecilie ; Fitzpatrick, Mike ; Ha, Yong-Sox ; Hoeck, Richard ; Huber, Felix Stephan ; Kanai, Yoshiko ; Kinoshita, Suchan ; Nader ; Neuhaus, Itty ; Sachs, Bernhard ; Siden, Ann-Sofi ; Téllez, Javier
Studio Artists 1993-1994, P.S. 1 Museum - The Cocktower, New York, 1994
Engels
boek